New Geophysical Mechanism Driving Major Species Extinction Events - Herndon, J. Marvin (European Journal of Applied Sciences, 2024)
Numerous attempts to describe the factors underlying the five major species-extinction events over the last 500 million years have led to coincidences, but to no underlying scientific basis. The principal reason for failure to understand is that the geoscience community has, since 1940, built scientific understanding upon a flawed basis. Here I provide a brief recitation of the more correct scientific basis, and upon that basis I disclose the underlying mechanism, connected to reversals and excursions of the geomagnetic field, that is the foundation for essentially all major non-anthropogenic species extinction events.